Synthesis, characterization and thermal behaviour of solid-state compounds of 4-methoxybenzoate with lanthanum (III) and trivalent lighter lanthanides - Rodrigues, E. C. [UNESP]; Siqueira, A. B. [UNESP]; Ionashiro, E. Y. [UNESP]; Bannach, Gilbert [UNESP]; Ionashiro, Massao [UNESP] (Editora Unesp, 2006)
Compostos M L foram sintetizados no estado sólido, onde M representa os íons trivalentes La, Ce, Pr, Nd e Sm, e L é o ânion 4 metoxibenzoato. Esses compostos foram caracterizados e estudados, utilizando-se as técnicas de difração de raios x pelo método do pó, espectroscopia na região do infravermelho, complexometria, termogravimetriaanálise térmica diferencial simultânea (TGDTA) e DSC. Os resultados permitiram obter informações com respeito à estequiometria, desidratação, transformação polimórfica, ligação metal- ligante, comportamento térmico e decomposição térmica.

Solid-state M-4-MeO-Bz compounds, where M stands for trivalent La, Ce, Pr, Nd and Sm and 4-MeO-Bz is 4-methoxybenzoate, have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to information about the composition, dehydration, polymorphic transformation, ligand's denticity, thermal behaviour and thermal decomposition of the isolated compounds.
Síntese, caracterização e comportamento térmico dos 4-metoxibenzoatos de lantânio (III) e lantanídeos leves trivalentes
Keywords: lantanídeos leves; 4; metoxibenzoato; caracterização e comportamento térmico; lighter lanthanides; 4-methoxybenzoate; characterization; thermal behaviour